2018
DOI: 10.1108/ijced-08-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of two interventions to support reading comprehension in primary-aged students

Abstract: Purpose-The purpose of this paper is to explore the explicit teaching of information text schema with vocabulary instruction to primary-aged students in Hong Kong international education. Design/methodology/approach-Data were collected through three quasi-experimental studies with different age groups and participants. Each study divided participants into two randomly assigned groups, either informational texts (IT) or vocabulary building (VB). Impact was evaluated with gain scores on a standardized reading co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Linguistic schema is an individual knowledge base for the reading comprehension process which activates background knowledge from schemata to support reading problem-solving (Freebody and Anderson, 1983; Hebert et al, 2016). It mainly works on cognitive reading abilities and cognitive affect (Cain et al, 2004; Sorrell and Brown, 2018). As for cognitive reading abilities, past studies showed that linguistic schema enhances readers’ first language (L1) reading comprehension abilities (e.g., inference, main idea abstraction) through meaning-based interpretations of the printed text (e.g., Cain et al, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Linguistic schema is an individual knowledge base for the reading comprehension process which activates background knowledge from schemata to support reading problem-solving (Freebody and Anderson, 1983; Hebert et al, 2016). It mainly works on cognitive reading abilities and cognitive affect (Cain et al, 2004; Sorrell and Brown, 2018). As for cognitive reading abilities, past studies showed that linguistic schema enhances readers’ first language (L1) reading comprehension abilities (e.g., inference, main idea abstraction) through meaning-based interpretations of the printed text (e.g., Cain et al, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is supported by the affordability of technology in society (Abidin et al, 2018;Visvizi et al, 2018). The era of computerization and the internet provides opportunities for the community to obtain information or literacy and used as a medium of learning and communication and can be used in social interaction (Jamaludin et al, 2020;ChanLin & Hung, 2018;Sorrell & Brown, 2018;Cetindamar Kozanoglu & Abedin, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Libraries as community information centers in promoting cultural cohesion, public and social services (Dowdell & Liew, 2019). Apart from as a source of information, it also aims to promote reading and provide reading resources for the community (Samsuddin et al, 2020) (Parekh & Mandalia, 2017) Reading materials that become public literacy in libraries are magazines and internet sites containing information (Sorrell & Brown, 2018).…”
Section: Introductionmentioning
confidence: 99%